Penguatan Identitas Dayak Muslim Katab Kebahan - Zaenuddin Hudi Prasojo (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
The globalization has been influential to not only those living in urban area but also those living in hinterland such as the Katab Kebahan Dayak of Melawi District in West Kalimantan. The community members, in fact, have actively engaged with the modernization to support their needs in daily life. Moreover, the Pemekaran Wilayah (the making of a new territory for a District) of Kabupaten Melawi has prompted social changes in the region and promoted social interactions among ethnic groups in the society. Politics of identity has shown to grow. In addition, many aspects of social changes including politics, education, economics and local culture have become influential to the growing of ethic awareness. The Katab Kebahan Dayak identity is a confirmation of the growing of ethnic awareness in the region.